The Soviet State Government And The Transformation Of Women In Public Life: Causes And Corrections - Ismoilova Nigorakhon Usmonjanovna (International Journal Of History And Political Sciences, 2025)
This article explores the transformation of women’s social status and public engagement in Uzbekistan during the 1920s and 1930s under Soviet rule. Based on archival materials, statistical data, and historical studies, the research analyzes the state policies aimed at women’s emancipation, the establishment of women’s departments, and the promotion of female participation in education, production, and cultural life. The study highlights multiple institutional mechanisms such as women’s departments, red teahouses, literacy schools, pedagogical institutes, and Atinoyi schools that shaped women’s cultural and political integration. It also examines the contradictions of Soviet gender policy, including administrative-command practices, ideological pressure, repression of traditional female educators, and the liquidation of women’s departments. The article emphasizes that although the Soviet reforms increased women's access to education and public life, they simultaneously disrupted traditional social norms, generated new socio-psychological challenges, and often subordinated cultural reforms to ideological objectives. Through a critical analysis, the study demonstrates that the emancipation process produced both significant achievements and profound socio-cultural losses.